The Era of Longevity Transformation of Aging, Health and Wealth - Chen, Dongsheng (Springer Nature, 2023)
This is an open access book under CC BY-NC-ND. This open access book is a comprehensive solution proposed by Dr. Chen Dongsheng for the issues of medical care, pension, and fund raising in the era of longevity. This book studies the relationship among aging population, economic development, and business model innovation. It integrates multi-disciplinary, multi-industry, and multi-professional research and thinking to focus on how to meet the challenge of aging population from business perspective. The author analyzes the keys and experience for Taikang to get successful in this area. The arrival of the "Era of Longevity" not only creates new business opportunities, but also changes the economy, governance, and cultural ecology of the society. It is of interest to the readers in business and policy-making.